Священная книга оборотня: [роман] / Виктор Пелевин - Пелевин Виктор Олегович (Pocket book, 2013)
Экземпляры: Аб (20160406) / Инвентарный номер: 103977 / Цена: 50.00 / Авт.знак: П 24 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6